A Novel Training Program for Police Officers that Improves Interactions with Mentally Ill Individuals and is Cost-Effective - Krameddine, Yasmeen; DeMarco, David; Hassel, Robert; Silverstone, Peter H. (Frontiers in Psychiatry, 2013)
Police and law enforcement providers frequently come into contact with individuals who have psychiatric disorders, sometimes with tragic results. Repeated studies suggest that greater understanding of psychiatric conditions by police officers would be beneficial. Here we present a novel approach to training police officers to improve their interactions with those who might have a mental illness. This approach involved developing a carefully scripted role-play training, which involved police officers (n=663) interacting with highly trained actors during six realistic scenarios. The primary goal of the training was to improve empathy, communication skills, and the ability of officers to de-escalate potentially difficult situations. Uniquely, feedback was given to officers after each scenario by several individuals including experienced police officers, a mental health professional, and by the actors involved (with insights such as “this is how you made me feel”). Results showed that there were no changes in attitudes of the police towards the mentally ill comparing data at baseline and at 6 months after the training in those who completed both ratings (n=170). In contrast, there were significant improvements in directly measured behaviours (n=142) as well as in indirect measurements of behaviour throughout the police force. Thus, compared to previous years, there was a significant increase in the recognition of mental health issues as a reason for a call (40%), improved efficiency in dealing with mental health issues, and a decrease in weapon or physical interactions with mentally ill individuals. The training cost was $120 per officer but led to significant cost savings (more than $80,000) in the following 6 months. In conclusion, this novel one-day training course significantly changed behaviour of police officers in meaningful ways and also led to cost savings. We propose that this training model could be adopted by other police agencies.